ANALISIS DETERMINAN CAPITAL STRUCTURE DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Cynthia Cynthia; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding the influence of tangibility, profitability, and business risk on capital structure with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sample in this study was taken by purposive sampling method with a sample size of 258 data. This study uses multiple regression analysis and moderated regression analysis assisted by using EViews 11 Student Lite and Microsoft Excel 2010. The results of this study are tangibility and profitability have a positive and significant effect on capital structure, business risk has no significant effect on capital structure, firm size as a moderating variable weakens the positive relationship between tangibility and capital structure, firm size as a moderating variable weakens the positive relationship between profitability and capital structure, firm size as moderating variable cannot moderate the relationship of business risk on capital structure. The implication of this research is there is a need for proper composition of debt and equity in the company's financial in order to achieve a good and optimal capital structure.